Covid-19 Cases Growth and Business Continuity in Indonesia: A Causality Test - Silvi Asna Prestianawati; Axellina Muara Setyanti (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
The objective of this study is to examine the causality between Covid-19 cases growth and business continuity in Indonesia, thus can be formulated the post-Covid business strategies. The Covid-19 cases are modeled into ‘daily case’ and ‘active case’, while business continuity proxied with human mobility to grocery and pharmacy, also to retail and recreation. Using daily data ranging from March to December 2020, the Granger causality results show that there is a bidirectional causality between daily case and grocery-pharmacy business, whereas interestingly there is a unidirectional relationship from retail-recreation business to daily case. In active case model, author found a unidirectional causality from active case to both grocery-pharmacy and retail-recreation business. This research may be used to improve business strategy in order to maintain the business life during the Covid-19 Pandemic in Indonesia.